Perbandingan Kurikulum Mentoring Al-Islam dan Kemuhammadiyahan antara tahun 2008 dan 2015 di Universitas Muhammadiyah Surakarta - Rohmah, Iftihatur, Dra. Mahasri Shobahiya, M.Ag (2017)
Muhammadiyah Universityof Surakarta is a Muhammadiyah Higher Education which has distinctive features elyMentoringl-Islam and Kemuhammadiyahan. In the span of years old, Mentoring Al-Islam and Kemuhammadiyahan already changed riculumseveral times, specifically in 2001, 2003, 2008 and 2015. The author is interested in researching "The comparisonof curriculum of Mentoring Al-Islam and Kemuhammadiyahan between 2008 and 2015 at Muhammadiyah Universityof Surakarta". The question in this study is "What are the differences, similarities, advantages, and deficiencies of curriculum of Mentoring Al-Islam and Kemuhammadiyahan in 2008 and 2015?". The purpose of this study is to describe the differences, similarities, advantages, and deficiencies of curriculum of Mentoring Al-Islam and Kemuhammadiyahan between 2008 and 2015.This research is a field research using descriptive qualitative approach because the collected data is in the form of words. The primary data resource used is hand book of Mentoring Al-Islam and Kemuhammadiyahan year 2008 and 2015.Data collection uses the methods of documentation, interview, and observation.As the data analysis uses content analysis. In this research, author analyzes the curriculum content of Mentoring Al-Islam and Kemuhammadiyahan year 2008 and 2015 at Muhammadiyah Universityof Surakarta.The result of the research presents that the alteration of curriculum Mentoring Al-Islam and Kemuhammadiyahan from 2008 to 2015 is based on circumstances and conditions of mentees in ollowing the test of reading Al-Qur'an and praying which was done before the active time of academic activity at the first semester, where the outcome revealed that it was still a lot of them being not be able to read Al-Qur'an yet and their praying that have not yet appropriated with the guidance of Rasulullah saw. Therefore, the change of curriculum Mentoring Al-Islam and Kemuhammadiyahan in 2015 is more focused on both sides.For that reason, the change possibly will be more effective to be applied in implementation of mentoring Al-Islam and Kemuhammadiyahan at Muhammadi-yah Universityof Surakarta.Keyword: Curriculum, Mentoring Al-Islam and Kemuhammadiyahan.